END OF LIFE DECISION MAKING: THE INDIAN SCENARIO : - Saeed , Saadiya (Journal of Forensic Medicine and Toxicology, 2016)
Although death is an everyday occurrence in the critical care units, there is a discomfort in confronting mortality in 21st century society. Advance life support interventions have greatly improved the prospects of treating seriously ill patients, but at the same time futile prolonged life support interventions can make death painful and agonising.